Features of ethno-oriented language learning - Laguta , T.; Verzhanskaya , O. (New Collegium, 2021)
The article is devoted to the peculiarities of ethno-oriented language teaching of foreign students. The definition of communicative ethnostistics is given, its object and subject are considered. The urgency of the problem is substantiated. The aim of the work is to consider different styles of national communication, as well as the parameters that are used to describe the national style of communication. Two main types of language acquisition are considered − communicative and non-communicative. Listeners of the communicative type prefer an intuitive way of learning the language, they easily learn the language during verbal communication. In most cases, they do not need deep theoretical explanations of the language material; they work successfully when attention is directed not to the learning process itself, but to its content side. Students of the non-communicative type are more inclined to analyze linguistic material, to identify logical and grammatical patterns in the language. It is emphasized that taking into account the ethnopsychological characteristics, mentality, national and cultural experience of representatives of different countries contributes to the organization of an effective educational process in a foreign audience and high-quality preparation of foreign students for successful communication. It is concluded that the national traditions of education and the associated styles of language acquisition must be taken into account already in teaching the Ukrainian language at the preparatory stage, which will optimize the process of learning the Ukrainian language. An ethno-oriented approach to teaching Ukrainian as a foreign language will allow teachers to adequately understand foreign students; to determine the effectiveness of the most acceptable forms and methods of teaching for representatives of a certain ethnic group; provide concrete assistance in solving problems of adaptation to a new socio-cultural environment; identify the difficulties that representatives of different ethnic groups face during language acquisition. Ethno-oriented education covers the interaction of the native and foreign (Ukrainian) languages in the cultural and educational space.